Glucodynamics of long‐acting basal insulin peglispro compared with insulin glargine at steady state in patients with type 1 diabetes: substudy of a randomized crossover trial. Issue 11 (20th June 2016) - Morrow, L. A.; Hompesch, M.; Jacober, S. J.; Leng Choi, S.; Qu, Y.; Sinha, V. P.
Abstract : Aims: To compare, in an open‐label, randomized, crossover phase II substudy, the glucodynamics of insulin glargine and those of basal insulin peglispro (BIL) in patients with type 1 diabetes. Methods: Patients (n = 23) underwent 24‐h euglycaemic clamps after 8 weeks of treatment with glargine or with BIL. Clinically‐titrated basal insulin doses (BIL group 16–64 U; glargine group 19–60 U) were administered on the morning of the clamp. Results: At baseline, the patients' mean ± standard deviation (s.d.) body mass index was 26.78 ± 4.20 kg/m 2 and glycated haemoglobin was 7.69 ± 0.99%. The mean ± s.d. endpoint dose for the BIL group was 0.42 ± 0.13 U/kg and for the glargine group was 0.42 ± 0.10. The daily mean ± s.d. blood glucose concentration was 7.7 ± 1.2 in the BIL group and 7.9 ± 1.2 mmol/l in the glargine group (p = 0.641). The mean ± s.d. total and nocturnal hypoglycaemia rates/30 days were 2.7 ± 2.3 and 0.5 ± 0.8, respectively, for the BIL group, and 3.0 ± 2.4 and 0.7 ± 1.1, respectively, for the glargine group (p = 0.112 and 0.428). The mean glucose infusion rate (GIR) normalized to insulin unit was lower for BIL than for glargine. One patient in the glargine group and eight patients in the BIL group had minimal (<0.8 g/kg) GIRs over 24 h. The mean ± s.d. total glucose infused over 24 h (GTOT (0–24) ) was 1.22 ± 0.82 g/kg in the BIL group and 1.90 ± 1.01 g/kg in the glargine group (p = 0.002). The mean ± s.d. total glucose infused during hours 0–6 (GTOT (0–6) ) was 0.21 ± 0.22 in the BIL group and 0.41 ± 0.22 g/kg in the glargine group (p < 0.001), while the mean total glucose infused during hours 18–24 (GTOT (18–24) ) in the BIL group was 0.28 ± 0.18 g/kg and in the glargine group was 0.35 ± 0.23 g/kg (p = 0.198). The peak‐to‐trough ratio was 1.41 for BIL versus 2.22 for glargine. Conclusions: BIL has a flatter profile than glargine, with potentially more stable metabolic control. The lower GTOT (0–24) observed in the BIL group is consistent with BIL's reduced peripheral action.